Effect of Horndeski theory on weak deflection angle using the Gauss-Bonnet theorem - Övgün, Ali; Kumaran, Yashmitha; Javed, Wajiha; Abbas, Jameela (World Scientific Publ Co Pte Ltd, 2022)
The main goal of this paper is to study the weak gravitational lensing by Horndeski black hole in weak field approximation. In order to do so, we exploit the Gibbons-Werner method to the optical geometry of Horndeski black hole and implement the Gauss-Bonnet theorem to accomplish the deflection angle of light in weak field region. Furthermore, we have endeavored to extend the scale of our work by comprising the impact of plasma medium on the deflection angle as properly. Later, the graphical influence of the deflection angle of photon on Horndeski black hole in plasma and nonplasma medium is examined.
Keywords: Weak gravitational lensing; Horndeski black hole; deflection angle; Gauss-Bonnet theorem